PERAN DAN KIPRAH AKTIVIS DAN PEMIMPIN PEREMPUAN ACEH SELATAN PADA KONFLIK DAN PASCA KONFLIK ACEH - Analiansyah Analiansyah (Pusat Studi Wanita UIN Ar-Raniry, 2017)
The long conflict in Aceh, have men and women discouraged to take part in society. Nevertheless, there are still figures of women who want and dare to do community organizing until the era of Aceh Peace. This article explains what and how the role of some women figures in South Aceh, both as activists and women leaders. This ethnographic research and women's role show that women contribute greatly to development, even in difficult situations such as conflict.The roles are initiating and strengthening women's organizations, enhancing human resource capacity, empowering the economy, initiating organizations specifically dealing with women and children who are vulnerable to violence, facilitating and supporting women in the political sphere. The involvement of women figures is based on several factors: 1) Their concerns about the socio-political conditions of Aceh, 2) Disillusionment with the gender bias in society that makes the space for women in the public very limited.